Naturvetarna, ingenjörerna och valfrihetens samhälle: Rekrytering till teknik och naturvetenskap under svensk efterkrigstid - Lövheim, Daniel (Kriterium, 2016)
"Scientists, engineers, and a free-choice society is a book about control, largely the governing of children and young people in Sweden and the efforts made to persuade them to choose careers-and identities-in science and technology in the period 1950-2000. It is very much part of an interdisciplinary research tradition in which perspectives taken from the history of science and education are combined with theories from the field of governmentality studies. The book begins by describing a new societal problem that confronted Sweden, like so many other Western countries, in the immediate post-war years, namely a lack of engineers and scientists. The period from the outbreak of the Second World War to the mid fifties saw a new appreciation for scientific research and its application in both the military and civilian sectors. With the reconstruction of Europe and the Marshall Plan at its height in the fifties, technology and science became gradually associated with rising industrial productivity and with economic growth in general. By the sixties this had left national employment policy with some markedly pronounced objectives. By the end of the decade, it was obvious that the determination to increase student numbers in science and engineering ran contrary to other political ambitions, and did not sit well with the right of the individual to freedom of choice in education. The attempt to respect people's autonomy while at the same time enabling more of them study these particular disciplines shaped a distinct set of strategies that made up the 'positive exercise of power'-what might also be called liberal governing-in which the main idea was to encourage students to come to science and engineering of their own free will. The book goes on to demonstrate how this strategy of governing through individual autonomy would result in a series of specific measures in the seventies and on, including changes to the curricula and teaching materials, which were matched by activities outside the traditional bounds of learning such as a travelling science shows, advertising campaigns, and the construction of science and technology centres. The book also spells out the sheer reach of this recruitment policy. Many leading figures in Sweden set out to encourage people to become scientists and engineers-these were voices heard not only from government quarters, but also from industry and special interest groups. Scientists, engineers and a free-choice society does not set out to answer the question of how best to set about attracting young people into science and technology; rather, it is concerned with how that question has been answered by others, and what impact their responses have had on power relations between society and the individual, and indeed on the place of science and engineering education in the present.